Correction: Behaviour-based functional and dysfunctional strategies of medical students to cope with burnout - Erschens, Rebecca; Loda, Teresa; Herrmann-Werner, Anne; Keifenheim, Katharina Eva; Stuber, Felicitas; Zipfel, Stephan; Junne, Florian (Medical education online, 2019)
Behaviour-based functional and dysfunctional strategies of medical students to cope with burnout